Methods And Techniques of Teaching in Mathematics Lessons in Primary School and Their Positive and Negative Aspects (The Peerian Journal, 2022)
This article discusses some methods and techniques of teaching in mathematics lessons in primary school and identifies their positive and negative aspects.